PENGARUH FUNCTIONAL QUALITY DAN TECHNICAL QUALITY PADA CUSTOMER LOYALTY DENGAN TRUST DAN COMMITMENT SEBAGAI VARIABEL INTERVENING DI PT. AURA DESAIN MITRA KREASI - Novica Kusuma Sari (Jurnal Strategi Pemasaran, 2016)
This research aims to analyze the influence of Functional Quality and Technical Quality towards Customer Loyalty through Trust and Commitment as an Intervening Variabel at PT. Aura Desain Mitra Kreasi. This research will be conducted by distributing questionnaires to 46 respondents which are consumer of PT. Aura Desain Mitra Kreasi. Quantitative analysis with path analysis analysis model method were used for the technical analysis.The results of this study indicate that the functional quality influence positively and significantly related to trust, functional quality influence positively and not significantly related to commitment, technical quality influence positively and significantly related to trust, technical quality influence positively and not significantly related to commitment, trust influence positively and significantly related to commitment, trust and commitment influence positively and significantly related to customer loyalty.